Separación y purificación de células del tumor venéreo transmisible canino espontáneo, en gradiente de densidad de polisucrosa y diatrizoato de sodio - González, Carlos; Cepeda, Raquel; Flores, Estefanía; Cattaneo, Gino; Colarte, Karen (Avances en Ciencias Veterinarias, 2002)
The canine venereal transmissible tumor (TVT) is a non differentiated round cell neoplasm frequently described on mucous membranes, specially of genital organs. The allotransplantability of this tu-mor has drawn the attention of researchers interested in transplant rejection mechanisms and immune response. The cytology of this tumor is similar in some aspects to that of lymphocytes and macrophages, in fact it was formerly known as venereal lymphosarcoma or Sticker's sarcoma. More recently, immunophenotipic markers of histiocitic origin have been detected on TVT cells. However, these studies are not conclusive due to the fact that the tumor is normally infiltrated by numerous leucocyte cells, including histiocytes from the host that are not easily distinguished from tumor cells. In this work it is proposed that TVT cells can be separated, in tumor cell suspensions, from leucocytes in a density gradient. The results show that TVT cells can not only be separated from most leucocytes in a polysucrose and sodium diatrizoate gradient, but also that it is posible to improve the percentage of viability, possibly as damaged cells are easily destroyed by osmotic changes.